Combining Ability Analysis of Dry Matter Content, Reducing Sugars and Yield of Potato (Solanum tuberosum L.) Genotypes in Uganda - Muhumuza, Edgar; Edema, Richard; Namugga, Prossy; Barekye, Alex (Journal of Scientific Agriculture, 2020)
Potato (Solanum tuberosum L.) in Uganda is a major food and cash crop mainly grown in the highland regions by small-scale farmers. The increasing importance of potato as a processed product requires new varieties possessing quality processing attributes with acceptable yield. The objectives of this study were to estimate the combining ability effects for dry matter content, reducing sugars, and yield related traits in potato. Nineteen F1 families generated from eight parents using a half diallel mating design were evaluated for dry matter content, reducing sugars, average weight per tuber and total tuber yield at Kachwekano research station. Additive genetic effects were predominant for dry matter content while non-additive effects for the other traits. The GCA/SCA ratios were 0.58, 0.28, 0.17 and 0.44 for dry matter content, reducing sugars, average weight per tuber and total tuber yield respectively. Broad sense heritability estimates were 50.6% for dry matter content, 77.8% for reducing sugars, 90.3% for average weight per tuber and 29.5% for total tuber yield. Parents NAROPOT 3 and 395096.2 had desirable GCA effects for both dry matter content and reducing sugars. Families of nkrk19.17 x Rutuku had desirable SCA effects for dry matter content while Rutuku x 393077.54 and nkrk19.17 x 392657.8 had desirable SCA effects for reducing sugars. Additive genetic effects for dry matter content imply that, genetic gains can be achieved through different selection methods and trait transferred to the respective progenies. The selected parents and families will be subjected to further clonal evaluation and selection.